Relationship between spontaneous excretion of lower ureter stones with stone size and serum level of C-reactive protein - Deldadeh-Moghaddam, Hamid; Nasrollahi , Sama (International Journal Of Community Medicine And Public Health, 2023)
Background: According to the recent studies on patients with stones in the urinary system, the CRP serum levels can be useful in predicting the possibility of success in expectant treatment and spontaneous excretion of stone and thus, selecting the appropriate patient for this treatment approach; however the studies conducted in this field are inadequate and the results obtained are slightly contradictory. The aim of this study was to investigate the relationship between spontaneous excretion of lower ureter stones with stone size and serum level of C-reactive protein. Methods: This cross-sectional study has been done on 95 patients with lower ureter stone during 2020-2021. Information including gender, age, body mass index, stone size, spontaneous excretion of stone, and CRP serum level were extracted from the files of patients. The existence of stone and its characteristics have been confirmed using ultrasound. Results: The mean CRP serum level was 8.74±‏5.06 mg/l and the frequency of spontaneous stone excretion was 72.6% (n=69). CRP serum level was significantly lower in patients with spontaneous stone excretion (7.42 vs. 12.23 mg/l and p=0.001). The cut-off point of CRP serum level was 13.5 mg/l for patients with ureter stone size of 4-7 (with 84% sensitivity and 58% specificity) and for patients with ureter stone size of 7-10, it was 12.5 mg/l (with 83% sensitivity and 56% specificity). Conclusions: The results showed that there is a significant relationship between the CRP serum levels, along with stone size with spontaneous excretion of lower ureter stones.